1970
DOI: 10.3329/bjms.v10i2.7810
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant occurrence of canine transmigration and symmetrical agenesis of incisors – A case report

Abstract: Transmigration of mandibular canine is an unusual phenomenon characterized by movement of the impacted canine crossing the mandibular midline. Mandibular canine are rarely found impacted in a horizontal position in the mandible. Most of the time, this entity occurred as an isolated finding. However there are reports showing association of dentigerous cyst and a hyperdontia. The purpose of this report is to present a case of transmigrated canine associated with agenesis of mandibular both central incisors which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…as well as some orthodontic tooth movement in more severe cases. 39 Nagaveni et al 40 reported a rare occurrence of concomitant occurrence of canine transmigration and symmetrical agenesis of mandibular permanent incisors.…”
Section: Managementmentioning
confidence: 99%
“…as well as some orthodontic tooth movement in more severe cases. 39 Nagaveni et al 40 reported a rare occurrence of concomitant occurrence of canine transmigration and symmetrical agenesis of mandibular permanent incisors.…”
Section: Managementmentioning
confidence: 99%